Peran Guru Pendidikan Agama Islam Dalam Optimalisasi Kegiatan Keagamaan Di Madrasah Aliyah Negeri 1 Sumbawa Besar - Muhammad Zakoni (Al-Kindi, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in optimizing religious activities at Madrasah Aliyah Negeri 1 Sumbawa. The focus of this study is to identify the role of Islamic Religious Education teachers to optimize various forms of religious activities carried out, examine the strategies applied by PAI teachers in optimizing these activities, and analyze the supporting and inhibiting factors in their implementation. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that this study reveals the strategic role of Islamic Religious Education Teachers at Madrasah Aliyah Negeri 1 Sumbawa which is implemented in three main dimensions, namely, as a director, motivator and mentor in religious activities. Various religious activities that are optimized include congregational Dhuhur prayers, MMQ (Reading and Writing the Qur'an), commemoration of Islamic holidays, and religious extracurricular activities. Supporting factors in optimizing these religious activities include support from the family, school facilities, the availability of adequate facilities and infrastructure, and the role of PAI teachers. Meanwhile, the inhibiting factors include, lack of self-awareness, lack of student motivation, lack of control from teachers, time allocation problems and limited facilities and infrastructure. This study contributes to the development of strategies to improve the quality of religious activities in Islamic high schools.